(untitled) (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: This article is devoted to the study of the material composition of the Yastrebovsk deposits of the early Frasnian age of the crestal part of the Voronezh Anteclise and the characterization of the compiled lithological-facie maps of a scale of 1:200 000 and sedimentogenesis schemes. Methodology: In the course of the work, the main research method was lithological-facies analysis. As a result of studying the stone material and based on the description of the wells, lithogenetic types of sediments used for the construction of facie maps were identified. Results and discussions: As a result of a detailed lithological characterization of the main types of Yastrebovsk deposits, it was shown that the formation of the studied sediments over almost the entirety of the studied territory occurred under coastal-marine and shallow-marine conditions with weak and medium activity of the hydrodynamic regime. In the south-east of the Voronezh Anteclise the formation occurred under lagoon and delta conditions. Explosive volcanic activity was the determining factor of sedimentation in the south-east of the territory. Conclusions: Yastrebovsk deposits were formed under a warm moist climate with low-amplitude tectonic movements. At this time, the sea transgressed from the east, and ablation of terrigenous material occurred from the south and west. A characteristic feature of the Yastrebovsk deposits is an admixture of pyroclastic material from active volcanoes in the south-east of the territory. These results can be used during geological surveys in the studied area and become the basis for lithological-facie mapping of a scale of 1:200 000 throughout the territory of the Voronezh Anteclise.